2023
DOI: 10.3390/vaccines11071192
|View full text |Cite
|
Sign up to set email alerts
|

A Parent Version of the Motors of COVID-19 Vaccination Acceptance Scale for Assessing Parents’ Motivation to Have Their Children Vaccinated

Abstract: Parents’ motivation to vaccinate their children against coronavirus disease 2019 (COVID-19) plays a crucial role in the uptake of COVID-19 vaccines among children. The Motors of COVID-19 Vaccination Acceptance Scale (MoVac-COVID19S) is a valuable tool for assessing individuals’ vaccination-related attitudes and the factors influencing their decision to be vaccinated against COVID-19. This study adapted the MoVac-COVID19S to create a parent version (P-MoVac-COVID19S) and examined the psychometric soundness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 56 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…Second, the homogenous use of self-report survey for the TPB predictors, intention, and vaccination behavior could make our responses vulnerable to response bias (e.g., social desirability) and consistency tendency. 11 Third, selection bias may exist as only around 34% of invited participants who provided contact for our follow-up study eventually completed our survey at Time 2. Specifically, the communication and invitation process was conducted solely through WhatsApp, without any personal contact initiated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the homogenous use of self-report survey for the TPB predictors, intention, and vaccination behavior could make our responses vulnerable to response bias (e.g., social desirability) and consistency tendency. 11 Third, selection bias may exist as only around 34% of invited participants who provided contact for our follow-up study eventually completed our survey at Time 2. Specifically, the communication and invitation process was conducted solely through WhatsApp, without any personal contact initiated.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Prior studies have also found that parents’ intention to vaccinate children against COVID-19 was influenced by various factors, including a perception of threat from the pandemic as well as attitudes toward and knowledge about the vaccines. 10 , 11 In particular, the theory of planned behavior (TPB) has been used successfully to predict vaccination behaviors in general and parents’ intention to vaccinate their children against COVID-19. 12 , 13 However, no research has examined factors that predict parents’ decision to actually vaccinate their children against COVID-19.…”
mentioning
confidence: 99%
“…The nine-item P-MoVac-COVID19S [ 42 ] is built on a robust theoretical foundation, being an adaption of the well-established Motors of COVID-19 Vaccination Acceptance Scale [ 43 , 44 ], which is based on the cognitive model of empowerment (CME) [ 45 ]. In the CME, empowerment is considered an innate motivation that drives people to engage in purposeful behavior.…”
Section: Methodsmentioning
confidence: 99%
“…In the CME, empowerment is considered an innate motivation that drives people to engage in purposeful behavior. This motivation originates from four distinct cognitive processes, namely value formation (e.g., considering the purposes of vaccinating children and the value of this behavior), impact comprehension (e.g., the belief that COVID-19 vaccination is effective in protecting children against COVID-19 infection and reducing the risk of severe symptoms), knowledge acquisition (e.g., comprehension of information and knowledge of pediatric COVID-19 vaccination), and a sense of autonomy (e.g., the feeling of being able to freely decide whether to get their child vaccinated) [ 42 ]. The P-MoVac-COVID19S is rated on a 7-point Likert-type scale with endpoints ranging from 1 (strongly disagree) to 7 (strongly agree).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation